First record of Melanaphis donacis (Passerini, 1861) (Hemiptera: Aphididae) in México - Vanegas-Rico, Juan M.; Peña-Martínez, Rebeca; Muñoz-Viveros, Ana L. (Entomological Communications, 2023)
The aphid Melanaphis donacis (Passerini, 1861) (Hemiptera: Aphididae) is recorded in Mexico in seven locations in the Valley of Mexico Basin on the Poaceae Arundo donax, one of the most common host plants. Both the aphid and the host plant are species considered exotic to Mexico; especially A. donax is referred to as one of the hundred most important invasive alien species in the world and is also officially cited in Mexico. Observations and collections of both the aphid colonies and the host plant began in October 2022 to February 2023. The work includes the taxonomic determination of both the aphid and the host plant. Also reviewed of websites (www.naturalista.mx) where in two sites it was referred to in a preliminary way, without taxonomic certainty by a specialist. In addition to the worldwide distribution of the aphid species and its host plants. Parthenogenetic wingless and winged forms are presented and described in vivo, as well as in mounts of microscope slides. In all the cases observed in the field, a symbiotic association with ants of the species Linepithema humile Mayr, 1868 (Hymenoptera: Formicidae) is documented. Some natural enemies were obtained, such as Harmonia axididis (Palas, 1773) (Coleoptera: Coccinellidae); Scymninae, Chamaemyiidae and Syrphidae larvae, yet to be determined. It is suggested to increase the search both in other localities and in hosts potentially present in Mexico.